TOPICAL GELS FOR DRUG DELIVERY: RECENT ADVANCEMENTS IN FORMULATION AND FUTURE DIRECTIONS IN CLINICAL PRACTICE - Sadia Ahmed Zuberi; Fawaz Jaffar; Nousheen Alam; Samina Sheikh; Nimra Aamir; Hasnan Ali; Rahat Fatima Naqvi (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
The main intention behind this review is to provide updated information related to the recent developments in terms of novel topical preparations including the basic concepts of dermal drug delivery systems. Topical drug delivery systems especially gels have several advantages such as it provides prolonged application to the site of action ultimately improving the therapeutic effect. A gel is a semisolid combination of a three-dimensional matrix of cross-linked materials. The three dimensional matrix of gel is mainly composed of a gelling agent and water. This review highlights the fundamentals of gel formulation and the factors affecting, along with the classification, advantages, limitations, and applications of different types of pharmaceutical gels such as niosomal/proniosomal gel, emulgels, bigels, xerogels and aerogels, organogels and hydrogels.